2022
DOI: 10.1186/s43141-022-00447-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation and assessment of genetic stability in date palm as affected by chitosan and thidiazuron combinations

Abstract: Background Mass propagation of date palm has attracted the interest of commercial producers. However, this technique still faces many obstacles that hinder production. This study investigated the effect of chitosan (CHT) at various concentrations for the possibility to apply it in combination with thidiazuron (TDZ) on the growth and development of tissue cultures of Barhee cultivar. Results The results showed that CHT and TDZ on in vitro proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…After 3 hrs of incubation, isolate TS2 exhibited above 50% auto aggregation, which increased to 85% after 20 hrs. A similar result was observed by Lata et al [14] where P kudrivenzii isolated from mango pickle showed 87% auto aggregation after 24 hrs. High hydrophobicity-exhibiting strains have good adhesion properties to intestinal cells.…”
Section: Probiotic Featuressupporting
confidence: 88%
See 1 more Smart Citation
“…After 3 hrs of incubation, isolate TS2 exhibited above 50% auto aggregation, which increased to 85% after 20 hrs. A similar result was observed by Lata et al [14] where P kudrivenzii isolated from mango pickle showed 87% auto aggregation after 24 hrs. High hydrophobicity-exhibiting strains have good adhesion properties to intestinal cells.…”
Section: Probiotic Featuressupporting
confidence: 88%
“…The hemolytic activity was determined by inoculating the yeast isolate on blood agar plates containing sheep blood and incubated for 48 h at 30 °C. The development of a clear zone around the colony indicates a positive result [14]. Antibiotic resistance of the yeast isolate was performed by the disc diffusion method using different antibiotic discs such as Nystatin (50µg), Miconazole (10 µg), Clotrimazole (10 µg), Fluconazole (10µg), Ketoconazole (50 µg), Itraconazole (10 µg), Cefmetazole (10 µg) (Sigma Aldrich).The antibiotic discs were placed on yeast-inoculated YPD agar plates and incubated for 48 h at 30 °C, and a zone of inhibition was observed [15].…”
Section: Safety Assessmentmentioning
confidence: 99%
“…Given that M3 and M4 are unexpected morphotypes and would hardly arise under traditional sowing conditions, these results suggest that the presence of TDZ in vitro could be acting as an inducer of somaclonal variation, as has been observed in other works [13,86]. Thus, the indirect organogenesis processes that are observed from the calluses could give rise to new morphotypes that would be of commercial interest.…”
Section: Occurrence Of Unexpected Morphotypessupporting
confidence: 64%